If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7y+6-1=12y=
We move all terms to the left:
7y+6-1-(12y)=0
We add all the numbers together, and all the variables
-5y+5=0
We move all terms containing y to the left, all other terms to the right
-5y=-5
y=-5/-5
y=1
| 1.6=m/7 | | 14/n=27/63 | | 2-20z=2(-10z+1) | | 1/3x=5/6x-2 | | 1/4=x/6 | | 4(e+4)=2(17-e) | | -6(q+3)=-6q-18 | | a/2-2=-5 | | n/8+2=3 | | -9(3b+4)=-18b | | Y=100x+19.5 | | 4-3n=433 | | 3x-7=2x-0.5 | | -9(-4t-15)=9t | | 1/3y+2/4=3/4y-2/3 | | n/10-2=-3 | | -7-5f+8=7-5f | | 4n-12=-48 | | 19x+8=14x-23 | | Y=120-x | | 5j+10=7j | | s+20=12+s+8 | | 6x-8=20-x | | 10x=3x(-28) | | 5d=-135 | | 2=t+8/3 | | 2(6c+2)=4+12c | | 1/4(8b-12)=11 | | 93x=62x | | 4a-2a=12a-24 | | u-740=-230 | | 2.5b+(2b-90)+90+(b+45)=360 |